ChemInform Abstract: New Ideas for a 160 Years‐Old Reaction. Issue 18 (April 2016) - Mendonca, Gabriela F.; de Almeida, Leonardo S.; de Mattos, Marcio C. S.; Esteves, Pierre M.; Ribeiro, Rodrigo S.
Abstract: Review: 169 refs.